1995
DOI: 10.1037/0022-3514.69.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous self-descriptions and ethnic identities in individualistic and collectivistic cultures.

Abstract: The Twenty Statements Test (TST) was administered in Seoul and New York, to 454 students from 2 cultures that emphasize collectivism and individualism, respectively. Responses, coded into 33 categories, were classified as either abstract or specific and as either autonomous or social. These 2 dichotomies were more independent in Seoul than in New York. The New York sample included Asian American whose spontaneous social identities differed. They either never listed ethnicity-nationality on the TST, or listed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
227
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(243 citation statements)
references
References 18 publications
11
227
0
5
Order By: Relevance
“…(WAI) five times as they imagined themselves in the scene. The WAI inventory (Kuhn & McPartland, 1954) served as the primary measure of awareness of ethnicity following the procedure of Rhee, Uleman, Lee, and Roman (1995). In this approach, You are starting a new semester.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(WAI) five times as they imagined themselves in the scene. The WAI inventory (Kuhn & McPartland, 1954) served as the primary measure of awareness of ethnicity following the procedure of Rhee, Uleman, Lee, and Roman (1995). In this approach, You are starting a new semester.…”
Section: Methodsmentioning
confidence: 99%
“…All other self-descriptions were classified as ethnicity unrelated. A total ethnic self-awareness score was determined using the procedure of Rhee et al (1995) that codes all discrete references to ethnicity in each of the five responses to the WAI as a percentage. Respondents' percentage ethnicity-related scores were used in all subsequent analyses to operationalize self-awareness of ethnicity.…”
Section: Ethnicity Unrelatedmentioning
confidence: 99%
“…Rhee, Uleman, Lee and Roman (1995) examined self-descriptions (i.e., 'I am' statements) from participants in individualistic and collectivistic cultures. They found that participants who strongly identified as Asian Americans tended to generate a higher proportion of social, and lower proportion of autonomous, self-descriptions compared to European Americans.…”
Section: Cross-cultural Possible Selvesmentioning
confidence: 99%
“…It is commonly accepted that culture impacts on self-construal (Markus & Kitayama, 1991), influencing how we define ourselves (Rhee et al, 1995;Wang, 2001;2004) and how we remember our earliest (Wang, 2006) and most self-defining memories (Jobson & O'Kearney, 2008). In the field of autobiographical memory, it has been suggested that cultural life scripts organize the retrieval of memories across the lifespan, influencing the way people construct both their past (Berntsen & Rubin, 2004), and future (Berntsen & Bohn, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation